2005
DOI: 10.1088/0957-4484/16/6/055
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast carrier dynamics in InP photonic crystals

Abstract: Ultrafast time-resolved reflectivity investigations are performed on InP-based photonic crystals with a wide range of structural parameters. It is found that the structure plays a critical role in determining the recombination dynamics of the photo-injected charge carriers. For sufficiently large etched sidewall area densities the carrier lifetime is decreased to a level below 100 ps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
3
13
1
Order By: Relevance
“…Implantation in InP should result in similar activation levels as for GaAs, though the Si (n dopant) would have a higher activation compared to Be (p dopant) [33]. At the same time, non-radiative recombination for InP has been shown to be over an order of magnitude slower due to the positioning of surface trap defects within the bandgap [58], [59]. Our preliminary Poisson simulations show that it should be possible to attain inversion in QWs and lasing at room temperature in properly designed InP lateral junctions.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Implantation in InP should result in similar activation levels as for GaAs, though the Si (n dopant) would have a higher activation compared to Be (p dopant) [33]. At the same time, non-radiative recombination for InP has been shown to be over an order of magnitude slower due to the positioning of surface trap defects within the bandgap [58], [59]. Our preliminary Poisson simulations show that it should be possible to attain inversion in QWs and lasing at room temperature in properly designed InP lateral junctions.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Surface states promote free-carrier recombination in proportion to the surface area. Prior research has shown all-optical switching with cylindrical [15] and spherical [16] semiconductor nanostructures with large surface state densities can speed up recombination. This study uses spherical nanoparticles, having the higher surface-area-to-volume ratio of the two.…”
Section: Nanoparticle Free-carrier Dynamicsmentioning
confidence: 99%
“…We have performed pump-probe time-resolved reflectivity measurements at 810nm on pure InP PhC pads with various periods and air filling factors [80]. The pump and probe beam were focused at 45° and 0° angles of incidence, respectively.…”
Section: Device Characterizationmentioning
confidence: 99%